Effects of yeast beta-1,3/1,6-glucans on nutrient digestibility, intestinal functionality, and immune and antioxidant variables in growing dogs submitted to spay or neutering surgery - Renata Bacila Morais dos Santos de Souza; Eduarda Lorena Fernandes; Lorenna Nicole Araújo Santos; Laiane da Silva Lima; Heloísa Lara Silva; Thaila Cristina Putarov; Simone Gisele de Oliveira; Ananda Portella Félix (PLoS ONE, 2025)
This study aimed to assess the impact of yeast beta-1,3/1,6-glucans (BG) on apparent digestibility coefficients (ADC) of nutrients, intestinal fermentative metabolites, fecal microbiota profile, and immune and antioxidant variables in puppies before and after surgical challenge. Two treatments were evaluated: control, without, and test, with oral supplementation of 65 mg/kg body weight/day of purified BG from Saccharomyces cerevisiae for 120 days. For this, 16 growing Beagle dogs were distributed in a completely randomized design (n = 8/treatment). On day 31, dogs were submitted to spay or neutering surgery. Diet ADC and fecal characteristics analyses were performed on days 55–60. Fecal (days 0, 15, 30, 34, and 60) and blood (days 0, 30, 34, and 60) samples were collected to evaluate intestinal fermentative metabolites, fecal IgA and microbiota, intestinal permeability, and immune and antioxidant variables. On day 80, all dogs were vaccinated for rabies and blood samples were collected on day 120 to determine antibody titers. The supplementation of BG promoted an increase in fecal IgA concentrations on day 15 (P < 0.05) and an increase in fecal concentrations of butyrate (P < 0.05) when day 30 minus day 0 were compared. Dogs of the BG group presented higher fecal concentrations of serotonin (day 15), spermidine (days 15, 30, and 34), and a reduction in tyramine, histamine, and cadaverine on day 60 (P < 0.001). BG consumption promoted an increase in richness and a clear differentiation in the fecal microbiota profile on days 34 and 60 (P < 0.05). BG group also presented an increase in fecal Faecalibacterium, Blautia, and Turicibacter on day 34 (P < 0.05). Reduced glutathione and catalase activities were higher in the BG group (P < 0.05), regardless of the day. In conclusion, the supplementation of BG does not alter the ADC of nutrients, beneficially modulates the intestinal functionality, and stimulates the activity of antioxidant enzymes in growing dogs submitted to a surgical challenge.